Study on combustor in mini jet engine - Gao, Xuan (2013)
Mini turbojet engines can be widely used for unmanned aerial vehicles due to their main advantages of small size and relatively high propulsion. This study focuses on the reverse flow combustor in the mini jet engine. It mainly includes the experiments and numerical simulation. The experiments have been conducted in the test rig of jet engine and pressure, temperature, and emission gas concentration were measured by the probes at several key positions: compressor inlet, combustor inlet, turbine inlet and outlet, and exhaust nozzle outlet. These experimental data allow us to validate simulation results, thus helping to improve the current combustor modeling.